Burnout and Work Demands Predict Reduced Job Satisfaction in Health Professionals Working In a Surgery Clinic - Dragan Mijakoski; Jovanka Karadzinska-Bislimovska; Basarovska, Vera; Sasho Stoleski; Minov, Jordan (ID Design 2012/DOOEL Skopje, 2015)
BACKGROUND: Burnout syndrome develops in health professionals (HPs) as a result of exposure to chronic emotional and interpersonal workplace stressors. Research demonstrates the links between burnout, work demands, and job satisfaction in hospital HPs. AIMS: To examine the associations between burnout, work demands and job satisfaction, and to demonstrate the mediation effect of emotional exhaustion on the relationship between work demands and job satisfaction in surgery clinic HPs. METHODS: Maslach Burnout Inventory was used for assessment of burnout. Work demands and job satisfaction were measured with Hospital Experience Scale and Job Satisfaction Survey, respectively. In order to examine the role of emotional exhaustion, depersonalization, and work demands, controlling for age, hospital tenure, and unit tenure, a hierarchical multiple regression models were tested for each job satisfaction factor. RESULTS: Job satisfaction was negatively predicted by emotional exhaustion. Certain types of work demands negatively predicted different factors of job satisfaction. Emotional exhaustion was a significant partial mediator of the relationship between work demands and job satisfaction. CONCLUSIONS: Adequate management of work demands, particularly excessive workload, time pressure, and lack of staff can lead to prevention of burnout and reduced job satisfaction in surgery clinic HPs, and contribute to better quality of patient care.
Keywords: Burnout; Work demands; Job satisfaction; Multiple regression; Mediation; Health professionals; Surgery clinic